2013
DOI: 10.1140/epjb/e2013-31157-6
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of superconductivity in the extended Hubbard model

Abstract: A microscopic theory of superconductivity in the extended Hubbard model which takes into account the intersite Coulomb repulsion and electron-phonon interaction is developed in the limit of strong correlations. The Dyson equation for normal and pair Green functions expressed in terms of the Hubbard operators is derived. The self-energy is obtained in the noncrossing approximation. In the normal state, antiferromagnetic short-range correlations result in the electronic spectrum with a narrow bandwidth. We calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 95 publications
4
53
1
Order By: Relevance
“…As described in detail in Refs. [18,22], using the Mori-type projection method [20] we derive an exact representation for the GF (13) in the form of the Dyson equation…”
Section: B Green Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in detail in Refs. [18,22], using the Mori-type projection method [20] we derive an exact representation for the GF (13) in the form of the Dyson equation…”
Section: B Green Functionsmentioning
confidence: 99%
“…In our recent paper [18] we studied the extended Hubbard model in the limit of strong correlations by taking into account the CI V and electron-phonon coupling. It was found that d-wave pairing with high-T c is mediated by the strong kinematic interaction of electrons with spin fluctuations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the scenarios of the development of the theory is associated with the use of the atomic representation [72] and diagram technique for the Hubbard operators [73]. The models in which the Kohn-Luttinger renormalizations can be taken into account include the generalized t − J − V model [74][75][76] and the t − J * − V model with three-center interactions (the important role of such interactions in describing the superconducting state was studied in [77][78][79][80][81][82][83][84]). These models are effective low-energy versions of the ShubinVonsovsky model.…”
Section: T − J Modelmentioning
confidence: 99%
“…As a result, the contributions associated with the electron-phonon, spin-fluctuation, and charge-fluctuations contributions [25,26] had to be taken into account additionally to compensate the strong repulsion associated with the intersite Coulomb interaction of holes. It should be noted, however, that the Coulomb interaction potential between holes in different cells was chosen in [25,26] equal to V = 0.2 eV, which is much lower than the spinfluctuation pairing potential g sf = 1.5 eV caused by the kinematic interaction; it is only for this reason that the superconducting d-wave phase was preserved. Due to a stronger kinematic mechanism [4], Cooper pairing was also observed at comparatively high values of V .…”
Section: Introductionmentioning
confidence: 99%